1991
DOI: 10.1103/physrevlett.67.2573
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectrum of the high-temperature superconducting state

Abstract: Improved experimental conditions enabled us to increase the signal-to-noise ratio of the photoemission spectra for the superconducting state of Bi2Ca2SrCu20s, taken with high angular and energy resolution. This also enabled us to reveal a pronounced minimum that separates the two basic features of the spectrum, the narrow quasiparticle excitation peak and the still controversial broad band at lower kinetic energies. The minimum is approximately 3A below the Fermi level.PACS numbers: 74.70.Vy, 79.60.Cn High-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
51
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(62 citation statements)
references
References 16 publications
(30 reference statements)
11
51
0
Order By: Relevance
“…Already, results establishing a marked anisotropy in the gap at low temperatures have ruled out an isotropic s-wave symmetry order parameter. [8][9][10][11] Our main result is that, contrary to anisotropic-gap conventional superconductors such as lead, [12][13][14] the gap anisotropy of Bi 2 Sr 2 Ca 1 Cu 2 O 8+x increases with increasing temperature as one approaches the superconducting transition temperature, T c . This result was discovered by estimating the gap from angle-resolved photoemission data, using the BCS-like lineshape [15,16] and computer code of Olson, Lynch and Liu.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Already, results establishing a marked anisotropy in the gap at low temperatures have ruled out an isotropic s-wave symmetry order parameter. [8][9][10][11] Our main result is that, contrary to anisotropic-gap conventional superconductors such as lead, [12][13][14] the gap anisotropy of Bi 2 Sr 2 Ca 1 Cu 2 O 8+x increases with increasing temperature as one approaches the superconducting transition temperature, T c . This result was discovered by estimating the gap from angle-resolved photoemission data, using the BCS-like lineshape [15,16] and computer code of Olson, Lynch and Liu.…”
mentioning
confidence: 93%
“…The count rate in photoemission superconducting condensate spectral area at 36K was about 1 kHz. The main temperature-dependent features of these spectra include: A shift of the leading edge that reveals the opening of the superconducting gap; a photoemission superconducting condensate spectral area with an energy full width at half maximum of 25 meV is observed immediately below the leading edge; a dip at binding energy of about 80 meV [9,10] for temperatures up to 0.84T c . Note that along the Γ −M direction, the photoemission superconducting condensate spectral area has been reproducibly observed at temperatures within 2K of the transition temperature (T c ) of 83K, and disappears above T c .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoemission measurements have been carried out by a number of groups [67,7,[68][69][70], and there is broad agreement on a number of features of the energy dispersion and Fermi surfaces. Figure 6 shows a representative collection of the Fermi surfaces reported by different groups.…”
Section: Bi-2212mentioning
confidence: 99%
“…The early ARPES experiments observed that around the antinodal region, a sharp electron quasiparticle excitation peak develops at the lowest binding energy corresponding to the SC gap, and is followed by a dip and then a hump in the higher energies, giving rise to a striking peak-dip-hump (PDH) structure in the electron quasiparticle excitation spectrum [13][14][15][16][17][18][19][20][21] . In particular, this similar PDH structure has been observed in tunneling and Raman spectra [22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%